Mechano‐signalling pathways in an experimental intensive critical illness myopathy model. (24th April 2016) - Corpeno Kalamgi, Rebeca; Salah, Heba; Gastaldello, Stefano; Martinez‐Redondo, Vicente; Ruas, Jorge L.; Fury, Wen; Bai, Yu; Gromada, Jesper; Sartori, Roberta; Guttridge, Denis C.; Sandri, Marco; Larsson, Lars
Abstract : Key points: Using an experimental rat intensive care unit (ICU) model, not limited by early mortality, we have previously shown that passive mechanical loading attenuates the loss of muscle mass and force‐generation capacity associated with the ICU intervention. Mitochondrial dynamics have recently been shown to play a more important role in muscle atrophy than previously recognized. In this study we demonstrate that mitochondrial dynamics, as well as mitophagy, is affected by mechanosensing at the transcriptional level, and muscle changes induced by unloading are counteracted by passive mechanical loading. The recently discovered ubiquitin ligases Fbxo31 and SMART are induced by mechanical silencing, an induction that similarly is prevented by passive mechanical loading. Abstract: The complete loss of mechanical stimuli of skeletal muscles, i.e. loss of external strain related to weight bearing and internal strain related to activation of contractile proteins, in mechanically ventilated, deeply sedated and/or pharmacologically paralysed intensive care unit (ICU) patients is an important factor triggering the critical illness myopathy (CIM). Using a unique experimental ICU rat model, mimicking basic ICU conditions, we have recently shown that mechanical silencing is a dominant factor triggering the preferential loss of myosin, muscle atrophy and decreased specific force in fast‐ and slow‐twitch muscles and muscle fibres. The aim of this study is to gain improved understanding of the gene signature and molecular pathways regulating the process of mechanical activation of skeletal muscle that are affected by the ICU condition. We have focused on pathways controlling myofibrillar protein synthesis and degradation, mitochondrial homeostasis and apoptosis. We demonstrate that genes regulating mitochondrial dynamics, as well as mitophagy are induced by mechanical silencing and that these effects are counteracted by passive mechanical loading. In addition, the recently identified ubiquitin ligases Fbxo31 and SMART are induced by mechanical silencing, an induction that is reversed by passive mechanical loading. Thus, mechano‐cell signalling events are identified which may play an important role for the improved clinical outcomes reported in response to the early mobilization and physical therapy in immobilized ICU patients. Key points: Using an experimental rat intensive care unit (ICU) model, not limited by early mortality, we have previously shown that passive mechanical loading attenuates the loss of muscle mass and force‐generation capacity associated with the ICU intervention. Mitochondrial dynamics have recently been shown to play a more important role in muscle atrophy than previously recognized. In this study we demonstrate that mitochondrial dynamics, as well as mitophagy, is affected by mechanosensing at the transcriptional level, and muscle changes induced by unloading are counteracted by passive mechanical loading. The recently discovered ubiquitin ligases Fbxo31 and SMART are induced by mechanical silencing, an induction that similarly is prevented by passive mechanical loading.